1996
DOI: 10.1038/bjc.1996.33
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of vinblastine cytotoxicity by dilantin (phenytoin) or the protein phosphatase inhibitor okadaic acid involves the potentiation of anti-mitotic effects and induction of apoptosis in human tumour cells

Abstract: Summary Cellular insensitivity to vinca alkaloids is suggested to be primarily due to drug efflux by P-glycoprotein (P-gp). The anti-epileptic phenytoin (DPH), which does not bind to P-gp, can selectively enhance vincristine (VCR) cytotoxicity in wild-type (WT) or multidrug-resistant (MDR) cells. We now demonstrate that the protein phosphatase inhibitor okadaic acid (OKA) can mimic the effect of DPH by selectively enhancing cytotoxicity of vinblastine (VBL), but not taxol and doxorubicin, in human leukaemia HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Strikingly, increasing number of FM3A cells accumulated with a duplicated complement of DNA up to 48 h of noscapine treatment and then underwent death (data not shown). This pattern of cell death following a prior mitotic arrest is similar to those previously observed in cells treated with other anti-microtubule agents (2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Inhibition Of P34supporting
confidence: 71%
See 1 more Smart Citation
“…Strikingly, increasing number of FM3A cells accumulated with a duplicated complement of DNA up to 48 h of noscapine treatment and then underwent death (data not shown). This pattern of cell death following a prior mitotic arrest is similar to those previously observed in cells treated with other anti-microtubule agents (2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Inhibition Of P34supporting
confidence: 71%
“…paclitaxel, colchicine, vinca alkaloids, etc.) arrest at mitosis, resulting from the disruption of proper mitotic spindle formation, and then undergo apoptosis (2)(3)(4)(5)(6)(7)(8)(9)(10). The next question was whether the mitotic arrest and apoptosis caused by anti-microtubule agents were two intimately related events or two independent consequences of disrupting the normal physiological balance of microtubule dynamics.…”
mentioning
confidence: 99%
“…Although a possible relationship between apoptosis and protein phosphorylation has been suggested in some tumour cell lines [8][9][10], there is no direct evidence for a role of protein kinases and/or protein phosphatases in neuronal apoptosis. We have previously reported that exposure of cultured cerebellar granule neurons to very low concentrations (0.5-5 nM) of the protein phosphatase (PP) 1 and 2A inhibitor okadaic acid (OKA) [11,12], results in widespread neurotoxicity [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…3 These 2 new categories of CR are associated with improved outcome. 4,5 After extensive discussions, the panel agreed that PET-CT findings should not be formally incorporated into the response criteria for the assessment of the depth of response, but additional single-center studies to further investigate the methodology were encouraged. 3 The data presented by Zamagni et al suggest that PET negativity after ASCT could in the future be incorporated into the criteria for…”
Section: Philippe Moreau University Hospital Nantesmentioning
confidence: 99%
“…After all, vinca alkaloid-induced cell death is associated with microtubule disruption during mitosis. 4 Why hasn't this potential interaction been considered before? It is always easier to see the obvious in hindsight, and the mechanisms of action of the majority of chemotherapeutic agents are far from fully understood.…”
mentioning
confidence: 99%